A new displacement-based approach for pulsating tension load tests of post-installed anchors for the use in structural applications under seismic actions. (15th May 2020) - Stehle, Erik Johannes; Sharma, Akanshu
Highlights: Displacement-based approach for pulsating tension tests for post-installed anchors. Comparison with force-based approach according to current guidelines. Experimental tests following the two cyclic protocols. Testing of five different types of post-installed anchors. New procedure provides additional information on the seismic performance. Abstract: The usage of post-installed anchors in structural applications and seismic retrofit solutions has become more and more popular over the past decades. The current approaches for seismic assessment of post-installed anchors follow primarily a force-based approach and were developed focusing on non-structural applications. On the structural level, performance based approach is becoming increasingly popular and important for the seismic design of structures as well as for seismic retrofitting of structures. This approach targets on the performance objectives that are closely related to the displacement behavior rather than on specific load levels to allow a better balance between construction costs and safety of structures. This performance based approach is also reflected in recent guidelines for seismic testing of reinforced concrete (RC) structural components. Yet in anchor design and qualification, the main focus is on force-based test and assessment methods. Such force-controlled assessment procedures may not provide sufficient information required to assess the performance of anchorages in structural applications where anchorages are subjected to strong demands and might be pushed beyond their linear behavior range. In this paper, a new displacement-based approach for testing of post-installed anchors under seismic actions is introduced. With this new approach, it is possible to obtain the complete hysteretic behavior over the entire range of the load-displacement response. The test setup, cyclic test protocol and typical results of the tests performed on five different post-installed anchor types are described and discussed in the paper. The anchors are tested under pulsating tension loads following (i) the force-controlled protocol specified by the existing qualification guidelines, and (ii) the new displacement-controlled protocol recommended in this work, and the results of the tests are compared. The results of the tests following the displacement-controlled protocol are found to be more suitable for the assessment of anchors used in structural strengthening applications under seismic actions due to their ability to provide the full information required for characterization of the anchors under seismic loads. The proposed approach holds promise to replace/augment the current testing procedures for seismic assessment of post-installed anchors. Based on the evaluation of the experimental results new assessment conditions are being developed for the assessment of post-installed anchors under seismic actions that will be presented by the authors in a future paper.